Body Mapping: Visual research & transformative human experience - Orchard, Treena (Revista Mundaú, 2020)
This article explores body mapping, a participant-driven approach wherein people create richly illustrated life-size maps that articulate their embodied experiences relative to various issues. First developed in the global South as a means of community mobilization and advocacy regarding women’s health and HIV-related care needs, body mapping is now used by researchers, health practitioners, and community agencies globally to explore social determinants of health among diverse groups. This work is relevant to social science and health scholars, community agencies, and those in activist circles who are interested in using body mapping in their mindful academic and applied work.